Improving Students' Speaking Skills Through Authentic YouTube Listening Materials: A Lesson from the EXO Mansapro English Program - Duwi Puspita Sari; Mohammad Sofyan Adi Pranata (Global Education Journal, 2026)
This study aims to explore the application of authentic YouTube listening materials in improving students’ speaking skills in the EXO Mansapro English Program. A qualitative case study design was employed to gain an in-depth understanding of the instructional process and students’ learning experiences within a specific non-formal EFL context. The participants consisted of five female students with varying levels of speaking proficiency, selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation to capture the natural dynamics of the teaching and learning process. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing and verification. The findings reveal that the integration of authentic YouTube listening materials positively influenced students’ speaking development in three major aspects: pronunciation, confidence, and motivation. Exposure to natural speech from native speakers enhanced students’ awareness of pronunciation, stress, and intonation patterns. Furthermore, video-based input provided contextualized linguistic models that reduced speaking anxiety and increased students’ confidence during oral practice. The engaging and relevant nature of YouTube content also fostered higher motivation and active participation in classroom discussions. The discussion highlights that authentic YouTube listening materials function not only as a source of meaningful linguistic input but also as affective support that promotes a more engaging and supportive learning environment. In conclusion, integrating authentic YouTube listening materials can serve as an effective pedagogical strategy for enhancing speaking skills in non-formal EFL programs.